Effects of soil and dietary exposures to Ag nanoparticles and AgNO3 in the terrestrial isopod Porcellionides pruinosus - Tourinho, Paula S.
The effects of Ag-NPs and AgNO3 on the isopod Porcellionides pruinosus were determined upon soil and dietary exposures. Isopods avoided Ag in soil, with EC50 values of ~16.0 and 14.0 mg Ag/kg for Ag-NPs and AgNO3, respectively. Feeding inhibition tests in soil showed EC50s for effects on consumption ratio of 127 and 56.7 mg Ag/kg, respectively. Although similar EC50s for effects on biomass were observed for nanoparticulate and ionic Ag (114 and 120 mg Ag/kg dry soil, respectively), at higher concentrations greater biomass loss was found for AgNO3. Upon dietary exposure, AgNO3 was more toxic, with EC50 for effects on biomass change being >1500 and 233 mg Ag/kg for Ag-NPs and AgNO3, respectively. The difference in toxicity between Ag-NPs and AgNO3 could not be explained from Ag body concentrations. This suggests that the relation between toxicity and bioavailability of Ag-NPs differs from that of ionic Ag in soils.